A short-circuit current limiting partitioning method based on graph theory search - Hao, Wenbin; Xia, Chun; Wang, Biao; Tang, Lun; Li, Bo; Wang, Xiaoxu (Dianli Xitong Baohu yu Kongzhi, 2015)
Breaking part of 500 kV/220 kV electromagnetic loop network and 220 kV network partition operation is an important measure to limit the short-circuit current of 220 kV bus. For the limitations of partitioning scheme relying on experience, this paper presents a grid partitioning algorithm about short-circuit current limitations. The goal of this method is to balance 500 kV transformer load, taking into account the constraints such as short-circuit current, lines' transmission power, substations' power, network topology and line power flow. This problem is solved by graph theory search and Visual Studio calling PSASP. Based on the data of a city power grid plan of 2015, the grid partitioning results show that the proposed algorithm is effective.